Characterization of BRCA1-deficient premalignant tissues and cancers identifies Plekha5 as a tumor metastasis suppressor - Jianlin Liu (Nature Portfolio, 2020)
Single-cell whole-exome sequencing is a powerful method for deciphering intratumor heterogeneity and identifying cancer drivers. Here, the authors analyze SNVs and CNVs simultaneously in bulk and single cells of BRCA1-associated breast tissues and cancers and show that Plekha5 deficiency promotes metastasis.